Lacticaseibacillus casei CNCM I-5663 supplementation maintained muscle mass in a model of frail rodents - Giron, Muriel; Thomas, Muriel; Jarzaguet, Marianne; Mayeur, Camille; Ferrere, Gladys; Noordine, Marie-Louise; Bornes, Stéphanie; Dardevet, Dominique; Chassard, Christophe; Savary-Auzeloux, Isabelle (Frontiers in Nutrition, 2022)
The aim of our work was to identify a probiotic-based strategy for maintaining muscle anabolism in the elderly. In previous research, we found that individuals experiencing short bowel syndrome (SBS) after an intestinal resection displayed beneficial metabolic adjustments that were mediated by their gut microbes. Thus, these bacteria could potentially be used to elicit similar positive effects in elderly people, who often have low food intake and thus develop sarcopenia. Gut bacterial strains from an SBS patient were evaluated for their ability to (1) maintain Caenorhabditis elegans survival and muscle structure and (2) promote protein anabolism in a model of frail rodents (18-month-old rats on a food-restricted diet: 75% of ad libitum consumption). We screened a first set of bacteria in C. elegans and selected two Lacticaseibacillus casei strains (62 and 63) for further testing in the rat model. We had four experimental groups: control rats on an ad libitum diet (AL); non-supplemented rats on the food-restricted diet (R); and two sets of food-restricted rats that received a daily supplement of one of the strains ( 109 CFU; R+62 and R+63). We measured lean mass, protein metabolism, insulin resistance, cecal short-chain fatty acids (SCFAs), and SCFA receptor expression in the gut. Food restriction led to decreased muscle mass (-10% vs. AL [p < 0.05]). Supplementation with strain 63 tempered this effect (-2% vs. AL [p > 0.1]). The mechanism appeared to be the stimulation of the insulin-sensitive p-S6/S6 and p-eIF2α/eIF2α ratios, which were similar in the R+63 and AL groups (p > 0.1) but lower in the R group (p < 0.05). We hypothesize that greater SCFA receptor sensitivity in the R+63 group promoted gut-muscle cross talk (GPR41: +40% and GPR43: +47% vs. R [p < 0.05]). Hence, strain 63 could be used in association with other nutritional strategies and exercise regimes to limit sarcopenia in frail elderly people.